The fourth president : possibilities for neighbourhood organising and change in suburban South Africa. - Prangley, Anthony (My University, 2012)
This research report examines the nature of middle class activism in Melville, Johannesburg. It makes a contribution towards filling the gap on suburban activism in post-Apartheid South Africa. This report also makes a contribution towards the evolution of international thinking around ‘your square mile’ and local development and contributes towards the growing literature around building more participatory democracy. It also makes a contribution towards integrating the social science literature that tends to focus on ‘structure’ and the literature in the management/leadership sciences that focuses on ‘agency’. The leaders interviewed in Melville describe their primary motivations and these are coded and described. They emphasise meaning oriented motivations for themselves and instrumental oriented motivations when considering others based on Klandermans (2003) categories of motivation to participate. Leaders described the features of activities and these are categorized. An important finding is the relative importance of value polarities and working with the state in Melville when compared with the literature on participation. A core part of citizens’ experience of a country is at the local neighbourhood level. We need to find ways to build the field and practice of contextual local neighbourhood action in the current era that can help resolve some of the major problems that South Africa and other societies face.